Dynamics and development of an Andean ceremonial center. The case of Cahuachi - Bachir Bacha, Aïcha (2007)
On the southern coast of Peru, the famous site of Cahuachi, the greatest establishment of the ancient Nasca, is traditionally interpreted as either hosting an important population or an exclusive ceremonial centre and a pilgrimage destination. Recently, analysis of cultural material reveal the existence of residential sections in the interior of the temples. Archaeological remains, in particular those excavated on periphery of the great monuments show proofs of permanent domestic life. The architectural organization of the ceremonial center tends toward enclosed and isolated spaces, far from the idea of an urban form. These elements pull us to change our mind about the function of this site. n the southern coast of Peru, the famous site of Cahuachi, the greatest establishment of the ancient Nasca, is traditionally interpreted as either hosting an important population or an exclusive ceremonial centre and a pilgrimage destination. Recently, analysis of cultural material reveal the existence of residential sections in the interior of the temples. Archaeological remains, in particular those excavated on periphery of the great monuments show proofs of permanent domestic life. The architectural organization of the ceremonial center tends toward enclosed and isolated spaces, far from the idea of an urban form. These elements pull us to change our mind about the function of this site.